XIAP Restricts TNF- and RIP3-Dependent Cell Death and Inflammasome Activation - Yabal, M; Müller, N; Adler, H; Knies, N; Groß, C; Damgaard, R; Kanegane, H; Ringelhan, M; Kaufmann, T; Heikenwälder, M; Strasser, A; Groß, O; et al. (Elsevier, 2014)
X-linked inhibitor of apoptosis protein (XIAP) has been identified as a potent regulator of innate immune responses, and loss-of-function mutations inXIAP cause the development of the X-linked lymphoproliferative syndrome type 2 (XLP-2) in humans. Using gene-targeted mice, we show that loss of XIAPor deletion of its RING domain lead to excessive cell death and IL-1β secretion from dendritic cells triggered by diverse Toll-like receptor stimuli. Aberrant IL-1β secretion is TNF dependent and requires RIP3 but is independent of cIAP1/cIAP2. The observed cell death also requires TNF and RIP3 but proceeds independently of caspase-1/caspase-11 or caspase-8 function. Loss of XIAP results in aberrantly elevated ubiquitylation of RIP1 outside of TNFR complex I. Virally infected Xiap-/- mice present with symptoms reminiscent of XLP-2. Our data show that XIAP controls RIP3-dependent cell death and IL-1β secretion in response to TNF, which might contribute to hyperinflammation in patients with XLP-2. © 2014 The Authors.